From the American Epicenter: Coronavirus Disease 2019 in Patients with Inflammatory Bowel Disease in the New York City Metropolitan Area. Issue 5 (24th June 2020) - Axelrad, Jordan E; Malter, Lisa; Hong, Simon; Chang, Shannon; Bosworth, Brian; Hudesman, David
Abstract: Background: We aimed to characterize patients with inflammatory bowel disease (IBD) and novel coronavirus disease 2019 (COVID-19). Methods: We performed a case series of patients with IBD and confirmed or highly suspected COVID-19 to assess rates of severe outcomes. Results: We identified 83 patients with IBD with confirmed (54%) or highly suspected (46%) COVID-19. The overall hospitalization rate was 6%, generally comprising patients with active Crohn's disease or older men with comorbidities, and 1 patient expired. Discussion: In this series of patients with IBD, severe outcomes of COVID-19 were rare and comparable to similarly aged individuals in the general population.